Using Scrambled Pictures Media to Improve Students’ Writing Skill in Narrative Text - Anfinda Mutiara Kasih; Kurniawan Kurniawan (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2019)
The present Classroom Action Research (CAR) initiated when the researcher found the students at the eighth-grade students of SMP Juara Pekanbaru had low writing skills. This problem could be identified from their base scores below the standard minimum score (GPA). It was 64,06. The purpose of this research was to try to develop the students’ writing skill and to know the factors that influenced the changing of students’ writing skill. This research was conducted from March up to May 2019 in two cycles consisted of ten meetings. The participants of this research were 27 students of the Andalusia class. In improving the students’ writing skill, a narrative text was used as a learning media. The instruments used in this research were writing test, interview, field note and also observation list to help understand the phenomenon. This research showed that the students got the score 72,22 in cycle 1 dan 84,49 in cycle 2, especially on organization with an increase of 4,47. It could be seen that scrambled pictures media could improve the students’ writing skill.